Intra-Arterial Peptide Receptor Radionuclide Therapy for Neuroendocrine Tumor Liver Metastases - Ebbers, Sander C.; Barentsz, Maarten W.; Braat, Arthur J.A.T.; Lam, Marnix G.E.H. (Digestive Disease Interventions, 2019)
Purpose Currently, peptide receptor radionuclide therapy (PRRT) with lutetium-177 (177Lu)-DOTATATE is used in patients with progressive neuroendocrine neoplasms (NEN) as salvage therapy. The standard treatment schedule consists of multiple cycles of intravenous (IV) administration. However, patients with liver metastases suffer from reduced tumor targeting and worse response and survival. This review provides an overview of the available evidence on the intra-arterial (IA) administration of radionuclide-labeled somatostatin analogues.Methods Databases of PubMed and Embase were searched systematically in May 2018 for studies that addressed IA PRRT. Included studies were original research publications focusing on absorbed tumor dose or tumor response after IA administration of PRRT for NEN. Publications on combined PRRT with other therapies or treatment of nonhepatic sites were excluded. Included publications were critically appraised on quality and their results reported accordingly.Results Seven publications were included in this review, including a total of 114 patients treated IA with different types of radiopeptides. Objective response was seen in 13 to 69% of the patients and disease stabilization in 18 to 52%. Disease progression occurred in 0 to 29% of the patients. IA administration resulted in a 1.06 to 9.2-fold increase in tumor-to-nontumor dose ratios in liver tumors, while normal liver and kidney doses remained within expected ranges. The incidence of adverse events was comparable to IV administration.Conclusion There is limited evidence that IA application of PRRT results in higher tumor-to-non-tumor dose ratios compared with IV infusion. IA administration of 177Lu-DOTATATE seems to be a promising new improvement in current clinical practice, achieving a higher absorbed tumor dose in patients with hepatic metastases of NEN.
Keywords: intra-arterial; peptide receptor radionuclide therapy; neuroendocrine neoplasm; liver metastases; lutetium-177-DOTA-octreotate